2017
DOI: 10.3892/mmr.2017.8122
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine ameliorates contrast‑induced kidney injury in rats with unilateral hydronephrosis

Abstract: The aim of the present study was to investigate the protective effects of N-acetylcysteine (NAC) on contrast-induced acute kidney injury in rats with unilateral hyronephrosis. Eighty-two male Sprague Dawley rats were randomized to undergo sham operation (n=14) or unilateral ureteral obstruction (UUO) (n=68). After 3 weeks, the UUO animals were randomized to three groups: NAC gastric perfusion, UUO+iohexol+NAC (n=24); normal saline perfusion, UUO+iohexol (n=24); and controls, UUO (n=20). After 3 days, UUO+iohex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
(52 reference statements)
3
5
0
Order By: Relevance
“…In this work, after injection of Urografin, some tubules revealed destruction of the apical plasma membrane with obvious decrease of their height and displaying highly vacuolated cytoplasm with dark pyknotic nuclei. These results are in agreement with Kohli et al [23] and Xia et al [18] who reported similar results like destroyed microvilli, vacuolation of cytoplasm and renal tubular damage.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this work, after injection of Urografin, some tubules revealed destruction of the apical plasma membrane with obvious decrease of their height and displaying highly vacuolated cytoplasm with dark pyknotic nuclei. These results are in agreement with Kohli et al [23] and Xia et al [18] who reported similar results like destroyed microvilli, vacuolation of cytoplasm and renal tubular damage.…”
Section: Discussionsupporting
confidence: 92%
“…As a preventive tool from contrast-induced nephropathy, in the present work we tried to study N-Acetylcysteine protective effect and found that it decreased greatly most of the harmful effects of Urografin on the kidney tubules with apparent improvement in the histological renal picture. These results are in accordance with Xia et al [18] who stated that Acetylcysteine has apparently decreased apoptosis occurring in renal tubular cells of rats as a response to ureteric obstruction with CM , and ameliorates kidney injury.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations